THE POSTPONEMENT OF THE VILLAGE HEAD ELECTION IN HUTAGODANG VILLAGE FROM THE PERSPECTIVE OF LAW NUMBER 3 OF 2024 CONCERNING VILLAGES AND SIYĀSAH DUSTŪRIYYAH - Usman Ardiansyah; Ilhamsyah Pasaribu (Program Pascasarjana UIN Sumatera Utara, 2026)
The postponement of the Village Head election in Hutagodang Village, South Labuhanbatu Regency, has generated significant issues related to village governance, leadership legitimacy, and the practice of local democracy. This study aims to analyze the factors behind the postponement of the Village Head Election (Pilkades), its impact on village administration and community participation, and to examine the issue from the perspective of Law Number 3 of 2024 concerning Villages and siyāsah dustūriyyah. This research employs a qualitative field research approach with a descriptive-analytical design. Data were collected through interviews with members of the Hutagodang Village community, observations of village governance conditions, and an examination of regional government policy documents related to the election delay. The findings reveal that the postponement was influenced by regional government policies linking the Pilkades schedule to the stages of simultaneous General and Regional Elections, creating uncertainty regarding its implementation. The consequences include frequent changes of Acting Village Heads since 2021, declining public trust and participation, and emerging social tensions. From the perspective of siyāsah dustūriyyah, the prolonged delay contradicts the principles of deliberation (shūrā), justice, and public welfare, as legitimate leadership must arise from community consent